Transfer Pricing and Financial Performance: The Case of Algerian Companies - Ouelhadj, Anissa; Bouchetara, Mehdi; Zerouti, Messaoud (Ceny transferowe a wyniki finansowe: przypadek spółek algierskich)
The increase of international trade represents more than 60% of the international economy, which is more profitable within the same group, thus prompting the continuous search for satisfactory financial performance by companies. This paper investigates whether transfer pricing has a positive and significant impact on corporate group’s financial performance in Algeria, over a period of five years since 2016 with a quantitative approach and SPSS software. The authors tested the regression of transfer pricing variables (tax burden, firm size and leverage) with the financial performance of 60 companies of corporate groups operating in different sectors as a research sample and found that transfer pricing has a significant and positive impact on those companies at 10% error margin, despite the fact that only the company size has a significant positive impact on ROA of these companies in Algeria, with a margin error of 1%. However, the authors concluded that the bigger the company, the more it should pay attention to its transfer prices and their declarations to avoid any tax adjustment which can hinder its financial performance.
Financial Sciences. Nauki o Finansach, 2023, vol. 28, no. 1, s. 32-46
Keywords: transfer pricing; financial performance; corporate groups; ceny transferowe; wyniki finansowe; grupy kapitałowe